Meselect – A Rapid and Effective Method for the Separation of the Main Leaf Tissue Types - Svozil, Julia; Gruissem, Wilhelm; Baerenfaller, Katja (Frontiers in Plant Science, 2016)
Individual tissues of complex eukaryotic organisms have specific gene expression programs that control their functions. Therefore, tissue-specific molecular information is required to increase our understanding of tissue-specific processes. Established methods in plants to obtain specific tissues or cell types from their organ or tissue context typically require the enzymatic degradation of cell walls followed by fluorescence-activated cell sorting (FACS) using plants engineered for localized expression of green fluorescent protein. This has facilitated the acquisition of valuable data, mainly on root cell type-specific transcript and protein expression. However, FACS of different leaf cell types is difficult because of chlorophyll autofluorescence that interferes with the sorting process. Furthermore, the cell wall composition is different in each cell type. This results in long incubation times for refractory cell types, and cell sorting itself can take several hours. To overcome these limitations, we developed Meselect (mechanical separation of leaf compound tissues), a rapid and effective method for the separation of leaf epidermal, vascular and mesophyll tissues. Meselect is a novel combination of mechanical separation and rapid protoplasting, which benefits from the unique cell wall composition of the different tissue types. Meselect has several advantages over cell sorting: it does not require expensive equipment such as a cell sorter and does not depend on specific fluorescent reporter lines, the use of blenders as well as the inherent mixing of different cell types and of intact and damaged cells can be avoided, and the time between wounding of the leaf and freezing of the sample is short. The efficacy and specificity of the method to enrich the different leaf tissue types has been confirmed using Arabidopsis leaves, but it has also been successfully used for leaves of other plants such as tomato or cassava. The method is therefore useful for plant scientists investigating leaf development or responses to stimuli at the tissue-specific level.